Chirale Synthesebausteine aus Aminosäuren: Dihydrothiazol-Derivate (Δ4-Thiazoline) aus Cystein - Dieter Seebach; André Jeanguenat; Jürgen Schmidt; Thomas Maetzke (CHIMIA)
Reaction of cysteine with pivalaldehyde and protection at the nitrogen atom with benzyl chloroformate give the diastereomerically pure cyclic N,S-acetal 2 which is selectively oxidized to the sulfoxide 3. Thiazoline 5 is obtained after oxidative, electrochemically induced decarboxylation and subsequent elimination of acetic acid. The oxidation level of the sulfur can be varied (sulfide 6 and sulfone 7). The carboxylated thiazoline 9 is obtained in three steps from 3 via esterification, Pummerer rearrangement, and elimination of the silyloxy intermediate. – These dihydrothiazole heterocycles with one or two stereogenic centres offer a new perspective to the use of cysteine as a chiral building block.